Introduction to Scholastic Theology - Leinsle, Ulrich Gottfried (Book collections on Project MUSE., 2010)
Reading Introduction to Scholastic Theology is an adventure, as it guides readers through the beginnings of scholastic theology in the works of the Fathers, on to Early Scholasticism, High Scholasticism, scholastic thought in a time of paradigm shifts (14-15th century) and its fate during Humanism and Reformation, to the beginnings of the Enlightenment, and Neo-Scholasticism in the nineteenth century. --Book Jacket.